2019
DOI: 10.3389/fmats.2019.00151
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Biodegradable Polymers for the Conservation of Cultural Heritage

Abstract: The use of polymers for conservation of cultural heritage is related to the possibility to slow down or stop natural deterioration which, in many cases, corresponds to stopping the entrance of liquid water and to favor spontaneous water vapor removal. Unfortunately, hydrophobicity is generally favored by surface roughness and thus competitive with transparency. It is therefore important to find an optimal balance hydrophobicity, transparency and durability (especially to photooxidation). However, polymers typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…The increase of the viscosity must be, then, correlated with an increase of the molecular weight or with a formation of some cross-links or some branching during the reprocessing. PBAT is, indeed, prone to form crosslinks during degradation [ 19 , 20 , 21 , 33 ], and the branching is the first step in forming cross-linked structures. No cross-links were revealed for the PLA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase of the viscosity must be, then, correlated with an increase of the molecular weight or with a formation of some cross-links or some branching during the reprocessing. PBAT is, indeed, prone to form crosslinks during degradation [ 19 , 20 , 21 , 33 ], and the branching is the first step in forming cross-linked structures. No cross-links were revealed for the PLA.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanical properties, namely elastic modulus (E), tensile strength (TS) and elongation at break (EB), of unprocessed Ecovio are reported in Table 2 [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that nanocomposites prepared with clays, when exposed to UV irradiation, degrade much faster than polymers as such [ 21–26 ] and this behavior has been attributed mainly to the pro‐oxidant effect of the impurities of the transition metals present in the clays. On the other hand, PBAT shows a poor photo‐oxidation behavior [ 27,28 ] and a complex photo‐oxidation mechanism. Indeed, the photo‐oxidation induces both decrease of the molecular weight and formation of branching.…”
Section: Introductionmentioning
confidence: 99%
“…The use of polymers for outdoor applications is strongly dependent on their durability, which is their capability to withstand the degradation phenomena. One of the main degradation phenomena is obviously represented by photooxidation, however it is not usually enough to provide polymer systems with good resistance to photooxidation, but it is also important to link this with the functional needs related to the specific application; furthermore, in some cases (such as, for instance, in cultural heritage conservation) features such as hydrophobicity and transparency should be granted 1 .…”
Section: Introductionmentioning
confidence: 99%